(untitled) (Journal of the College of Basic Education, 2023)
Returning to the heritage in all its forms and chapters and according to what is required by necessity, whether literary or cognitive, is one of the things that deserves standing and praising it, because this heritage is the product of a nation and its originality, and we cannot enrich this product and this originality without digging well in its secret and public caches alike and discussing it with discussion A scholarly view that does not look at it with the eye of sanctification and divinity, but rather with the eye of modernization, development and continuity. Standing before this legacy and not adding to it is the death and extinction not only of the heritage but of our contemporary discourse, because any discourse in existence if it does not obtain some kind of addition will remain rigid in its place and thus lose its luster. And its effectiveness, but this does not mean, of course, that the inherited be burdened with more than it responds to, nor does it rely on its superficialities and ignore its savings and hidden things. Among the important studies that took place in this space is the study of Jaber Asfour (The Concept of Poetry), in which he made a distinguished effort by shedding light on the concept of poetry among some ancient critics, trying to highlight the developed cultural awareness that our ancestors took refuge in.